Website-Based Sales Information System at One Coffe Point Cafe - Dwiki Aulia Akbar; Ika Ratna Indra Astutik (Universitas Muhammadiyah Sidoarjo, 2021)
. Currently the development of technology in the marketing of a product is growing and easy, The amount of competition in the business world requires business actors to develop an innovation and strategy in marketing their products so that they can increase sales results. One of them is by using website media in their marketing process and data processing. With good data processing and marketing, it can be an evaluation for entrepreneurs in their product development and marketing. So that it can reduce unwanted things in the future. The purpose of this research is to facilitate entrepreneurs in marketing and processing data from their business by creating a website-based sales information system. While the method used is the waterfall method where this method has several stages of manufacture from start to finish and in making it is made as attractive as possible. The results of this study are the website can provide all information about the point one coffee cafe to customers and can be accessed anywhere from the device available by the customer.